SimYA: A virtual reality–based construction studio simulator. (June 2022) - Şahbaz, Eray
In architectural education, generally experience is the most permanent way to learn professional skills. However, perhaps as a result of modern education, it is not possible to learn everything about the building by experience. SimYA project aims to help the development of a new generation construction studio based on learning by doing and experiencing in architectural education by using virtual reality (VR) technologies. Within the scope of the project, an interactive VR-based computer simulation (SimYA) developed to demonstrate basic construction elements such as foundations, walls, and roofs. The effectiveness of the SimYA against the traditional method has been tested with a scientific experiment. A total of 32 volunteer architecture students participated in the experiment. The participants were divided into two equal groups within the scope of the experiment. These groups were named as SimYA and control group in a way to be compatible with their related method. First, a pre-test was applied in order to evaluate the current knowledge of the groups. After that, the first group was taught with the VR supported SimYA program and the second group was taught with the traditional method. According to test results, the success rate of the SimYA group increased from 5.63% to 74.86%, and the success rate of the control group increased from 3.12% to 57.95%. These results indicate that the SimYA project has achieved the targeted success. It is thought that placing the building elements and materials in the virtual environment with student's own hands and receiving visual and audio information from the interactive building elements are an important factor in this success.